2002
DOI: 10.1074/jbc.m109801200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Matrix Metalloproteinase-2 by Overexpression of Manganese Superoxide Dismutase in Human Breast Cancer MCF-7 Cells Involves Reactive Oxygen Species

Abstract: Cancer metastasis is a multistep process that includes invasion of cancer cells into blood vessels, traveling of these cells in the circulation system, and proliferation and eventual formation of a metastatic tumor at distal tissues. Among these steps, the first step of cancer cell invasion is a critical point for cancer metastasis. A current hypothesis proposes that remodeling of the extracellular matrix is a required process for cancer cell invasion (1, 2).The process of extracellular matrix remodeling happe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(117 citation statements)
references
References 41 publications
7
110
0
Order By: Relevance
“…CO also upregulates SOD2, which scavenges superoxide, augments mitochondrial H 2 O 2 release, and may modulate redox signaling (Zhang et al, 2002). In cardiomyocytes, mitochondrial CC-1 uptake in the presence of CO was blocked by mitochondrialtargeted catalase.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…CO also upregulates SOD2, which scavenges superoxide, augments mitochondrial H 2 O 2 release, and may modulate redox signaling (Zhang et al, 2002). In cardiomyocytes, mitochondrial CC-1 uptake in the presence of CO was blocked by mitochondrialtargeted catalase.…”
Section: Discussionmentioning
confidence: 89%
“…The CO to cytochrome a 3 stoichiometry was too low to compromise aerobic energy production to the point of damage, and indicated a high gain of mitochondrial biogenesis to mitochondrial oxidation-reduction state. For instance, the spectral data suggest that the CO:O 2 ratio adjusts electron transport in conjunction with the Q cycle to regulate superoxide production and the H 2 O 2 leak rate via SOD2 (Trumpower, 1990;Zhang et al, 2002) (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…An early report on MCF-7 breast cancer cells indicated that MnSOD induced MMP2 expression by regulation of intracellular ROS (21). Another report showed that MMP2 transcription was directly upregulated by FoxM1 and that the invasion of glioma cells was enhanced by FoxM1-induced MMP2 expression (30).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang and colleagues showed activation of MMP2 by MnSOD in human breast cancer MCF-7 cells via the regulation of intracellular reactive oxygen species (ROS; ref. 21). A study on immunodeficient mice showed that MnSOD promoted the metastastic potential of fibrosarcoma cells via increased levels of MMP1 mRNA (22).…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione peroxidase (GPX) and catalase (CAT) are enzymes that cause the inactivation of MMP-2 and decrease mass migration of breast cancer cells which are associated with MMPs through the reduction and elimination of hydrogen peroxide (Zhang et al, 2002).…”
Section: Oxidative Stress and Breast Cancermentioning
confidence: 99%